Estudio de Factibilidad para la implementación de un sistema informático de orientación vocacional para la Unidad Educativa Simón Bolívar de Pimocha - Franco Ortiz, Alvaro Guillermo (2018)
In recent times worldwide and national technology covers much of our time, work and study using this technology in various areas especially in education. Therefore, education can not be left behind, since nowadays these processes are carried out manually, which is why too much time is generated and applied by applying these processes, this implementation of the computer system will benefit both the administration of the educational unit of the millennium "SIMÓN BOLÍVAR" and the students of this institution to give and collect information among themselves. In the part of the evaluation of psychopedagogical tests in the area of ​​vocational guidance, this process is still done manually, which affects in several aspects such as time, resources, etc. In the institution, in the administration and acquisition of print sheets for the tests can be used in other areas to benefit the institution. This study is created with the purpose of guiding the third year students of basic of the institution in the choice of their specialties, seeing each one of their abilities / weaknesses and their preferences in each of the inculcated subjects. Also to the students of the third year of the baccalaureate, applying information, evaluation and orientation of the careers applicable to their specialization profile. Regarding the administration department, having an automated information system would greatly help students and teachers in the quality service provided to each one of them.